Political and Community Logics of Emergent Disease Vaccine Deployment: Anthropological Insights from DRC, Uganda and Tanzania - Lees, Shelley; Alcayna-Stevens, Lys; Bowmer, Alex; Marchant, Mark; Enria, Luisa; Vanderslott, Samantha (Anthropologica)

(untitled) (University of Victoria, 2024)
With a growing number of emerging infectious diseases and the rapid development of vaccines during epidemics and pandemics, public health officials at the global and national level have reported concerns about vaccine hesitancy, often attributing this to a problem of misinformation and poor understanding of risk. However, social scientists have found that vaccination perceptions are complex and multi-faceted. By focusing on the historical, cultural and political influences that affect vaccine acceptance, as well as social justice questions that examine the fair distribution of vaccines, we explore the political and community logics of vaccine deployment using a case study approach. We found differing logics depending on the vaccine and the context and argue that political and community logics come to the forefront during outbreaks as vaccine strategies often are imposed—in different ways—by the Global North. We suggest that, prior to the development and deployment of new vaccines for emergent diseases in the Global South, political level and community logics must be acknowledged and engaged with.